Business model renewal and ambidexterity: structural alteration and strategy formation process during transition to a Cloud business model. (June 2014) - Khanagha, Saeed; Volberda, Henk; Oshri, Ilan; Spieth, Patrick; Schneckenberg, Dirk; Ricart, Joan E.
<x xml:space="preserve">Abstract</x> This paper presents the findings of a longitudinal study of a large corporation's transition to a new business model in the face of a major transformation in the ICT industry brought about by Cloud computing. We build theory on the process of business model innovation through a qualitative study that investigates how an established firm organizes for an emerging business model. Contrary to previous findings that presented spatial separation as the optimal structural approach for dealing with two competing business models, our findings indicate a need for recursive iterations between different modes of separated and integrated structures in line with the emergent nature of strategic intent toward the new business models. Our analyses reveal strategy formation to be a collective experimental learning process revolving around a number of alternative strategic intentions ranging from incremental evolution and transformation to complete replacement of the existing business model. Given the fundamental differences in the nature and requirements of those alternative intents, iterations between different structural modes and differing combinations proved to be crucial in enabling the organization to make transition to the new business model.